Optimization of a Recyclable Sodium-Based Heterogeneous Catalyst for Efficient DMC Synthesis Under Mild Conditions - Byeon, Jae-Yong; Yoon, Sang-Hyeok; Lee, Ru-Ri; Kim, Beom-Seo; Nah, In Wook; Jung, Hyun Wook; Shim, Jae-Oh (한국화학공학회, 2026)
Dimethyl carbonate (DMC) is a green chemical with wide industrial applications. It is necessary to develop a method to produce DMC safely, eco-friendly, and economically. In this work, DMC was synthesized via transesterification of ethylene carbonate (EC) and methanol (MeOH) using a heterogeneous base catalyst combining sodium aluminate and cyanoguanidine (SC catalyst). Among the series, the optimized sodium aluminate–cyanoguanidine catalyst (denoted as SC-2, NaAlO2/cyanoguanidine weight ratio = 3:4) exhibited the highest activity, achieving a 73% DMC yield, which outperformed sodium aluminate (25%) and sodium carbonate (46%). This enhanced performance is attributed to synergistic effects that arise from structural and basicity enhancements. Under optimized conditions (40 ℃, 2 h, 0.5 wt% catalyst, EC: MeOH = 1:8), SC-2 achieved an 85% yield and demonstrated excellent reusability, with less than 20% yield loss over five cycles.